Inequalities in morbidity in South Africa: A family perspective - Elizabeth Biney; Acheampong Yaw Amoateng; Olusegun Sunday Ewemooje (Elsevier, 2020)
South Africa is struggling to achieve sustainable development targets as the country faces a quadruple burden of diseases. Concerted efforts to realise good health for all people require evidence-based targeted interventions. This study aimed to investigate the relationship between living arrangements and self-reported ill-health among adults aged 15 years and older in South Africa. Analyses were based on a sample of 49,962 individuals drawn from the 2017 South African General Household Survey, using a multivariate regression technique to assess the distribution and predictors of ill-health. Composite indices of disease burdens were created using several related morbidities in each disease category. The findings confirm that health outcomes in South Africa vary by living arrangements of individuals, their socioeconomic status, and by the level of urbanisation or residence. It was found that women who are black, younger and less-educated, irrespective of their living arrangement, are particularly vulnerable to illhealth. Policy implications are discussed.